SĄDOWE USTALENIE OJCOSTWA W FEDERACJI ROSYJSKIEJ - Holewińska-Łapińska, Elżbieta (Zeszyty Prawnicze, 2017)
Judicial Establishing of Paternity in the Russian Federation Summary The article discusses the judicial establishing of paternity pursuant to the Family Code of the Russian Federation in force from March 1, 1996 against a background of former regulations of the Soviet Law starting from 1917. In the years 1917-1944 judicial establishing of paternity in USSR was admissible without restrictions. In the period from July 8, 1944 to October 1, 1968 prohibition of judicial establishing of paternity was in force. In the period from October 1, 1968 to March 1, 1996 establishing of paternity could occur if in a case one of the following was true: (1) A child’s mother and a defendant lived together before the birth of a child and managed a common household. (2) A child’s mother and a defendant raised a child together. (3) A child’s mother and a defendant provided jointly for a child. It was not required that a defendant contributed significantly to the cost of living of a child but that he did it systematically. (4) There was reliable evidence that a defendant admitted his paternity. If a child was born in the period from October 1, 1968 to March 1, 1996, his parentage was not as yet affiliated to a father, and a man whose paternity was to be established was alive - still one of the aforementioned conditions has to be proved in a lawsuit. Judicial establishing of paternity of a child who was born starting from March 1, 1996 may occur on a demand of a child’s mother, a man who claims he is a child’s father, a child’s custodian (guardian), a person who keeps a child, a child of age. Judicial establishing of paternity may be demanded in person by a parent who has turned fourteen. A child of age has to give his/her assent to establishing of paternity. If s/he was incapacitated - a consent should be given by a custodian or a care agency. One has to prove, presenting evidence of any nature, that this particular man is a father of a child. In practice evidence taken into account shall either prove the paternity in a scientifically dependable manner (a DNA test) or prove indirectly a validity of a suit (e.g. a child’s mother and a man pointed out as a father stayed in a common-law marriage during the period of a probable conception of a child). After father’s death a court may establish paternity on the grounds of the fact, that during his life a the said man expressed by his conduct a conviction that he believes himself a father of a child in question. If a child was born before October 1, 1968 additionally it has to be proven that a man deeming himself a father did keep his extra-marital child.